SIFAT FISIK DAN SENSORIS EMPEK-EMPEK IKAN LELE DUMBO (Clarias gariepinus) KERING REKONSTITUSI - , NURUL FAJRIYATI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The research was conducted to study the physical and sensory properties of reconstituted dried dumbo catfish (Clarias gariepinus) âempek-empekâ with addition tapioca flour. Various concentrations of tapioca flour in empek-empek were examine, i.e. 25 %, 50 %, 75 %, and 100 % of total 100 grams dumbo catfish. Physical properties were elasticity, % volum expansion level, color, and gels formed. The color, smell, texture, flavor, and preference of dumbo catfish empek-empek were examined by sensory test. The results indicated that dumbo catfish can be used for empek-empek material which was preferred by consumers. Addition of tapioca flour to processing influences characteristic of dried dumbo catfish empek-empek, i.e. moisture, protein, fat, and ash contents decreased by reducing of addition of tapioca flour, but carbohydrate content was increased by reducing of addition of tapioca flour. Elasticity, % volume expansion level, color of reconstituted dried dumbo catfish empek-empek were increased by reducing of addition tapioca flour. Microscopically gels formed to be seem more ordered and homogen with lower addition of tapioca flour. Addition of 100% tapioca flour yielded dumbo catfish empek-empek which was the panelist most preferred.